2017
DOI: 10.3389/fphys.2017.00919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Morinda citrifolia (Noni)-Enriched Diet on Hepatic Heat Shock Protein and Lipid Metabolism-Related Genes in Heat Stressed Broiler Chickens

Abstract: Heat stress (HS) has been reported to alter fat deposition in broilers, however the underlying molecular mechanisms are not well-defined. The objectives of the current study were, therefore: (1) to determine the effects of acute (2 h) and chronic (3 weeks) HS on the expression of key molecular signatures involved in hepatic lipogenic and lipolytic programs, and (2) to assess if diet supplementation with dried Noni medicinal plant (0.2% of the diet) modulates these effects. Broilers (480 males, 1 d) were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 94 publications
6
53
1
Order By: Relevance
“…ATP citrate lyase (ACLY), a cytosolic enzyme that catalyzes the generation of acetyl-CoA for both fatty acid and cholesterol synthesis is involved in do novo lipogenesis pathway [26]. And heat stress result in hepatic expression of key lipogenic proteins and increased ACLY expression in chicken [27]. The lanosterol synthase (LSS) is a well-known enzyme within the pathway of cholesterol biosynthesis, which catalyzes the reaction of conversion from 2,3-oxide-squalene to lanosterol [28].…”
Section: Discussionmentioning
confidence: 99%
“…ATP citrate lyase (ACLY), a cytosolic enzyme that catalyzes the generation of acetyl-CoA for both fatty acid and cholesterol synthesis is involved in do novo lipogenesis pathway [26]. And heat stress result in hepatic expression of key lipogenic proteins and increased ACLY expression in chicken [27]. The lanosterol synthase (LSS) is a well-known enzyme within the pathway of cholesterol biosynthesis, which catalyzes the reaction of conversion from 2,3-oxide-squalene to lanosterol [28].…”
Section: Discussionmentioning
confidence: 99%
“…In a study with heat stressed broilers, [60] found no effects of 2 g/kg dried Morinda fruit powderon feed intake and growth, but the supplementation improved the hepatic expression of heat shock protein in a time-specific manner, suggesting and egg production in Japanese quails. According to Sunder et al [65],there is a synergistic effect between Morinda extract and lactobacillus in terms of body weight gain, feed efficiency, immunomodulation and reduction of gut E. coli count in poultry, confirming the antimicrobial activity of Morinda products.…”
Section: Morinda Products In Poultry Feedingmentioning
confidence: 95%
“…Morinda supplementation showed immunomodulatory effects by increasing total leucocytes and inducing greater oxidative burst intensity by the primary neutrophil concentration, which improved resistance of cattle to disease in a high-risk population [7]. Quercetins, a bioactive ingredient in Morinda [59] has heat stress mediating effects in poultry [60]. According to Hong et al [14] the immune enhancing activity of noni fruit extract is due to its modulatory effect on immune cells, induction of the expression of proinflammatory cytokine genes and inhibition of the expression of interleukin (IL10).The concentration of phytoconstituents in Morinda depends on several factors including the plant part and stage of maturity [61,62].…”
Section: Common Phytoconstituents and Modes Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting study showed that heat stress could up regulate the hepatic expression of heat shock protein in broilers. Also reported that heat stress induced the hepatic lipogenesis in chickens and they mentioned that this effect probably mediated by heat shock protein (Flees et al, 2017). In the literature there was no information concerning the effects of dietary oils inclusion on heat shock proteins and blood lipid attributes.…”
Section: Introductionmentioning
confidence: 99%